Aplikasi Pengontrol Robot Mobil Menggunakan Suara Berbasis Android - I Putu Aix Cendana; Anak Agung Ketut Agung Cahyawan Wiranatha; Kadek Suar Wibawa (Jurnal Ilmiah Merpati (Menara Penelitian Akademika Teknologi Informasi), 2017)
Robot Mobil is a robot that is made using wheel drive equipment, so it can move and move position. Automobile robots can move and move positions automatically not only according to embedded programs, but can also be controlled directly remotely. Android-Based Robot Car-Based Controller App is a built-in app for controlling the movement of car robots using voice commands. Applications are made using Google's Speech API to convert voice-to-text inputs before being sent to a car robot. Applications can be used by connecting to the Internet (online) to be able to use Google's Speech API. The app can also be used without being connected to the Internet (offline) by downloading offline speech recognition language first. Response to the movement of the car robot after the spoken word on the application an average of 7 seconds online and 5 seconds offline in real-time.